1988
DOI: 10.1002/jcp.1041340212
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of intracellular and trans‐acting differentiation‐inducing activity in human promyelocytic leukemia HL‐60 cells: Its possible involvement in process of cell differentiation from a commitment step to a phenotype‐expression step

Abstract: We previously reported that human promyelocytic leukemia HL-60 cells, when treated with various inducers in magnesium-deficient medium, became committed to differentiate but did not express the differentiation-related phenotypes (Okazaki et al., J. Cell. Physiol., 131:50-57, 1987). In the present study we demonstrated the existence of an intracellular differentiation-inducing activity (int-DIA) in differentiation-committed phenotype-nonexpressing HL-60 cells by using cybrid formation between untreated HL-60 ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1989
1989
2005
2005

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…To date, there are no studies that have yet been reported on the use of cybridization to direct chondrogenic differentiation. Nevertheless, previous studies have shown that cybridization could be used to induce teratocarcinoma cells to express myoblast function [218, 219] as well as direct erythroid [220, 221] and myeloid [222] differentiation.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…To date, there are no studies that have yet been reported on the use of cybridization to direct chondrogenic differentiation. Nevertheless, previous studies have shown that cybridization could be used to induce teratocarcinoma cells to express myoblast function [218, 219] as well as direct erythroid [220, 221] and myeloid [222] differentiation.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…Together with the findings that uremic serum confers l,25-(OH)2D3 resistance upon the HL-60 cells in the induction of cell differentiation and of 24-hydroxylation activity partly by decreasing the l,25-(OH)2D3 receptor content, these data raise the possibility that a possible decrease in the intracellular cAM P level might contribute to the l,25-(OH)2D3 resistance observed in the uremic serumtreated cells. An incubation time of 2 days was selected to measure intracellular cAMP levels because, around 2 days of exposure to l,25-(OH)2D3, the cells so treated progress from the commitment step to the phenotype-expression step [28]. As shown in figure 4, intracellular cAMP levels in the uremic serum-treated cells (n = 4) exhibited 9.85 ± 1.16 pmol/107 cells as compared with 13.7 ±3.20 pmol/107 cells of the normal serum-treated cells (n = 3, p<0.05).…”
Section: Effect O F Uremic Serum On Intracellular Camp Content O F Hlmentioning
confidence: 99%
“…To date, there are no studies that have reported the use of cybridization to direct stem cell differentiation. Previous studies have shown that cybridization could be used to induce teratocarcinoma cells to express myoblast function (Iwakura et al 1985;Tosu et al 1988), as well as direct erythroid (Watanabe et al 1985(Watanabe et al , 1988 and myeloid (Okazaki et al 1988) differentiation.…”
Section: Cybridization To Direct Stem Cell Differentiationmentioning
confidence: 99%